Tecovirimat is active against various MPXV strains, while cidofovir, brincidofovir, trifluridine, and gemcitabine have no detectable MPXV-specific antiviral activity - Higashi-Kuwata, Nobuyo; Kato, Mariko; Hattori, Shin-ichiro; Takamatsu, Yuki; Mitsuya, Hiroaki (Virus research, 2025)
•Compounds reportedly active against MPXVs are in controversy and are revisited.•Only tecovirimat among agents tested here exhibits MPXV-specific antiviral activity.•Apparent anti-MPXV activity of agents except tecovirimat results from their toxicity.•Novel agents more potent than tecovirimat are urgently needed for controlling mpox. In treating patients with mpox, current treatment options are limited, with tecovirimat (TEC) being one of the few available. TEC has been approved by the European Medicines Agency (EMA) for treating patients with mpox and is in clinical use in Europe and Japan. However, following exposure to TEC, TEC-resistant variants such as A290V-containing variant (MPXVRTEC/A290V) emerge quickly. In such cases involving MPXVRTEC/A290V, alternative agents such as brincidofovir (BCV) have been used, although their efficacy remains controversial and their anti-MPXV activity is yet to be clearly defined. In the present work, we evaluated the anti-MPXV features of five agents (TEC; cidofovir, CDV; BCV; trifluridine, TFT; and gemcitabine, dFdC) reportedly active against various MPXV strains including MPXVSPL2A7, MPXVZr-599, MPXVLiberia and MPXVRTEC/A290V, employing cell-based quantitative assays using multiple target cell types such as VeroE6 cells as well as morphometric assays focusing on their cytostatic and cytotoxic natures. The EC50 values of TEC against MPXVSPL2A7, MPXVZr-599, and MPXVLiberia were 0.001, 0.005, and 0.004 µM, respectively, without tangible cytotoxicity, while that against MPXVRTEC/A290V was ∼130-fold greater with 0.13 µM. The EC50 values of CDV, BCV, TFT, and dFdC against MPXVRTEC/A290V were 18, 1.8, 3.8, and 0.02 µM, respectively; however, the apparent anti-MPXV activity of these four agents was highly associated with their cytotoxicity as they were examined with qualitative and quantitative cell-based-morphometric assays. The data strongly show that none the four agents examined exhibited significant anti-MPXV activity and indicate that effective anti-MPXV agents active against wild-type and drug-resistant variants are urgently needed.